Tooth preparations: science & art. Author: Clovis Pagani, Co-workers: Eduardo Galera da Silva, Daniel Maranha da Rocha. Hanover Park, Illinois: Quintessence; 2017. ISBN: 978-1-78698-001-4. - José Roberto Rodrigues (Brazilian Dental Science)
Tooth preparations: science & art Autor